2022
DOI: 10.3389/fvets.2022.919904
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics-Based Study of Differentially Expressed Genes Related to Fat Deposition in Tibetan and Yorkshire Pigs

Abstract: Fat deposition traits are one of the key factors in pig production and breeding. The fat deposition capacity of pigs mainly affects the quality of pork and pig productivity. The aim of this study was to analyze the differential expression of mRNA levels in dorsal adipose tissue of Tibetan and York pigs at different growth stages using transcriptomic data to estimate key genes that regulate fat deposition in pigs. The results showed that a total of 32,747 positively expressed genes were present in the dorsal ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…We focused on the 10 genes with the highest p -values in the transcriptome. Ten of these genes, including PVALB , THRSP ( 33 , 34 ), HOXA9 ( 35 ), EEPD1 ( 36 ), HOXA10 ( 37 ), and PDE4B ( 38 ) have been reported to be involved in fat deposition and meat quality. Through the PPI analysis, we found that PVALB gene was the top 1 hub gene.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the 10 genes with the highest p -values in the transcriptome. Ten of these genes, including PVALB , THRSP ( 33 , 34 ), HOXA9 ( 35 ), EEPD1 ( 36 ), HOXA10 ( 37 ), and PDE4B ( 38 ) have been reported to be involved in fat deposition and meat quality. Through the PPI analysis, we found that PVALB gene was the top 1 hub gene.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely distributed and is currently one of the most commonly raised pig breeds worldwide. Yorkshire pigs have excellent characteristics such as fast weight gain, high feed conversion rate, and high lean meat rate of carcasses ( Gong et al, 2022 ). At present, Tibetan pigs on the Tibetan plateau are raised mainly through stabling and half-stabling feeding, often grazing in the sports arena, and their feed, comprising grass, leaves, fruits, roots, and insects, is rich in fiber.…”
Section: Introductionmentioning
confidence: 99%
“…DEGs were identified between different comparison groups (WDL vs WGH, RSQ vs CRQ) using the DESeq2 package in R (version 4.2.1) based on negative binomial distribution. Considering previous studies [ 31 , 32 ] and our specific experimental situation, adjusted P -values ( P -adjust) < 0.05 and |log2FoldChange|> 0 were established as the thresholds for significance. Adjusted P -values were calculated using the Benjamini–Hochberg method.…”
Section: Methodsmentioning
confidence: 99%